FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2018 - eka marlinda; Muhammad Luthfi; Eka Sariningsih (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2022)
This study aims to determine the Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee on Audit Delay. This study uses data from the 2016-2018 Financial Statements. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange. Data collection method used in this study is purposive sampling method, which is the determination of samples based on the suitability of certain characteristics and criteria. Based on the purposive sampling method, obtained research samples were conducted on 135 samples of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. Hypothesis testing in this study was carried out by using multiple linear regression analysis methods in the application of the SPSS 20 program. The results showed that the Company Size variable significantly influenced audit delay with a significant value of 0.033. Company Age Variable influences audit delay with a significance value of 0.012. Auditor Opinion Variable influences Audit Delay with a significance value of 0.003. KAP Reputation Variable has no effect on Audit Delay with a significance value of 0.299. The Audit Committee variable does not affect the Audit Delay with a significance value of 0.059. Simultaneously the variables Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee have an influence on Audit Delay with a significance value of 0,000.Keywords:Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee, Audit Delay.This study aims to determine the Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee on Audit Delay. This study uses data from the 2016-2018 Financial Statements. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange. Data collection method used in this study is purposive sampling method, which is the determination of samples based on the suitability of certain characteristics and criteria. Based on the purposive sampling method, obtained research samples were conducted on 135 samples of manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2016-2018. Hypothesis testing in this study was carried out by using multiple linear regression analysis methods in the application of the SPSS 20 program. The results showed that the Company Size variable significantly influenced audit delay with a significant value of 0.033. Company Age Variable influences audit delay with a significance value of 0.012. Auditor Opinion Variable influences Audit Delay with a significance value of 0.003. KAP Reputation Variable has no effect on Audit Delay with a significance value of 0.299. The Audit Committee variable does not affect the Audit Delay with a significance value of 0.059. Simultaneously the variables Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee have an influence on Audit Delay with a significance value of 0,000.Keywords:Company Size, Company Age, Auditor Opinion, KAP Reputation, Audit Committee, Audit Delay.